2001
DOI: 10.1093/clinchem/47.4.673
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive, Automated Immunoassay for Immunoglobulin Free Light Chains in Serum and Urine

Abstract: Background: Bence Jones proteins or monoclonal immunoglobulin κ and λ free light chains (FLCs) are important markers for identifying and monitoring many patients with B-cell tumors. Automated immunoassays that measure FLCs in urine and serum have considerable clinical potential. Methods: Sheep antibodies, specific for FLCs, were prepared by immunization with pure κ and λ molecules and then adsorbed extensively against whole immunoglobulins. The antibodies were conjugated onto latex particles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
215
0
7

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 562 publications
(234 citation statements)
references
References 26 publications
3
215
0
7
Order By: Relevance
“…Patients with a biopsy-proven diagnosis of AL (n = 13) and NALCDD (n = 5) were randomly chosen for this study (Table I). Plasma samples collected from these patients were analyzed by the FLC assay (FREELITE TM , The Binding Site Ltd., Birmingham, UK) (Bradwell et al, 2001) on a Dade Behring BNII automated nephelometer. Diagnoses were obtained from the Dysproteinemia database and the patient medical history by following a protocol approved by the Mayo Institutional Review Board.…”
Section: Plasma Samplesmentioning
confidence: 99%
“…Patients with a biopsy-proven diagnosis of AL (n = 13) and NALCDD (n = 5) were randomly chosen for this study (Table I). Plasma samples collected from these patients were analyzed by the FLC assay (FREELITE TM , The Binding Site Ltd., Birmingham, UK) (Bradwell et al, 2001) on a Dade Behring BNII automated nephelometer. Diagnoses were obtained from the Dysproteinemia database and the patient medical history by following a protocol approved by the Mayo Institutional Review Board.…”
Section: Plasma Samplesmentioning
confidence: 99%
“…The assay thus detects only free circulating light chain monomers and dimers with minimal cross-reactivity with whole immunoglobulin. 3 Advantages of this investigation include technical simplicity and very high sensitivity of up to 100 times greater than serum or urine electrophoresis (EPP) with a limit of detection below that of the normal serum light chain level. The sFLC assay provides a readily obtainable and quantitative result that rapidly reflects changes in production of light chains by the aberrant plasma cell population due to the short half-life of free light chains in serum (2-6 h compared with 20-25 days for intact immunglobulin G when renal function is normal).…”
Section: Introductionmentioning
confidence: 99%
“…Serum free light chain (FLC) estimation. A new immunoassay can detect and quantify FLCs in serum with remarkable specificity and sensitivity (Bradwell et al, 2001). The assay gives a positive result (raised level of either kappa or lambda together with an altered ratio of free kappa to free lambda light chain) in 98% of patients with systemic AL amyloidosis (Lachmann et al, 2003), including those in whom a monoclonal immunoglobulin cannot be demonstrated by conventional means.…”
Section: Diagnostic Investigationsmentioning
confidence: 99%
“…The objective of chemotherapy in AL amyloidosis is to suppress production of amyloidogenic monoclonal immunoglobulin light chains as quickly and safely as possible, but the relative efficacies of different chemotherapy regimens have not been determined. Recent experience at the NAC suggests that treatment strategies in individual patients are presently best guided by their early effect on quantifiable measurements of circulating free immunoglobulin light chains (Bradwell et al, 2001;Lachmann et al, 2003). Although these patients were selected and had not been randomized to receive particular therapies, it is notable that neither the magnitude nor durability of the clonal disease responses differed significantly among patients who were treated with VAD, monthly intravenous IDM or stem cell transplantation.…”
Section: Overview Of Treatment Recommendationsmentioning
confidence: 99%